Reliability Analysis Based on Implementation of Loop Restoration Scheme and Proposed Additional Pick-Up Current Sensor in Distribution Network - Fauzi, M. Annas Albab, Ir. Jatmiko, M.T (2016)
Distribution system take the responsbility in electricity supply to customer. It mean the customer satisfication plays the main role and become the important part to electricity company. Therefore, the enhancement of the quality of distribution system is a must. Implementation of distribution feeder automation system (DFAS) through SCADA system become the best solution to customer satisfaction problems. It can result the improvement of reliability, consistent quality and high-tech services. Loop restoration strategy (LRS) is a special DFAS method in the feeder level which is used by electric utilities to improve distribution system reliability. The LRS is controlled and managed by its automatic control system (ACS). Thus, this paper try to proposed the ACS mechanism as the SCADA automation procedure. Furthermore, optimizing automation procedure in this paper is giong to present the utilize and combining the pick-up current alarm status with another type of alarm sensor that already used in SCADA master station. The implementation of pick-up current alarm status will give advantages due the autorecovery and automation performance. A step by step evaluating procedure is proposed in this paper asses the impact of the LRS and the combination of LRS and SCADA as the automation mechanism of distribution system and the analysis of the pick-up current alarm status in SCADA system.